Government Budget in Pandemic Period: A Note - Heru Subiyantoro (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Until now, the deficit is an unavoidable Government policy when preparing the budget. The reason for the Government to implement this policy is because the revenue side grew lower than the increase in the routine expenditure side. This situation requires the Government to carry out a contractionary policy by increasing spending to increase production so that economic growth also increases. The government implements macroeconomic policies by applying the precautionary principle, including in budget management so that there is no excessive deficit. At the same time, the government is also trying to anticipate the uncertain world economy. From 2020-2021, Indonesia experienced a period of the Covid-19 pandemic which resulted in slowing national economic growth. Government Regulations instead of Laws are used as the legal basis. Formulating extraordinary policies outside the usual running budget due to the Covid-19 pandemic has turned out to have resulted in better financial performance, and an increase in the quality of society.